A polydopamine layer as the nucleation center of MOF deposition on "inert" polymer surfaces to fabricate hierarchically structured porous films1. Issue 13 (14th February 2015) - Zhou, Meimei; Li, Jian; Zhang, Meng; Wang, Hui; Lan, Yue; Wu, Yi-nan; Li, Fengting; Li, Guangtao
<x xml:space="preserve">Abstract</x> Polydopamine could be used as an effective nucleation center for MOF deposition on "inert" polymer membranes, affording hierarchically structured porous films.